Analysis of Syntactic Structure of Coordination in EMMA by Jane Austen - Hidayah, Ari Nur, Dra. Malikatul Laila, M.Hum, Dr. Dwi Haryanti, M.Hum (2015)
This research paper focuses on syntactic structures of coordination in Emma novel written by Jane Austen. This research has three objectives: (1) To identify the types of constituents combined to form syntactic structures of coordination in Emma novel written by Jane Austen, (2) To identify the highest frequent of category being coordinated in syntactic structures of coordination, and (3) To describe the distribution of syntactic structures of coordination in Emma novel by Jane Austen. The object of the research is sentences having syntactic structures of coordination in chapter 1 of Emma novel written by Jane Austen, volume 1. The type of this research is descriptive qualitative research. To collect the data, the researcher used documentation method. The steps to analyze the data are reading, collecting, and numbering the data. To analyze the data, the researcher uses structural grammar by using Chinese boxes. The results show that: 1) the types of constituents being combined are categorized in three groups: words which are noun, adjective, verb, to infinitive, and adverb; phrases which are noun phrase, adjective phrase, verb phrase, infinitive phrase, and prepositional phrase; and clauses which are independent clause and dependent clause, 2) the highest frequent of category being coordinated in Emma novel written by Jane Austen is independent clauses that has 23, 33% (14 data), and 3) the distribution of syntactic structures of coordination in Emma novel by Jane Austen analyzed based on its function in sentence and phrase: three functions in sentence: as predicate and as complement (subjective and objective complement) and two functions in phrase: as head and as modifier. Keywords: Syntax, Structure of Coordination, Structural Grammar, Chinese Boxes.